PROFESSIONAL DEVELOPMENT: INTERRELATION OF RUSSIAN AND FOREIGN APPROACHES - A. Pashko (Publishing House of the State University of Management, 2016)
The article discusses a number of theoretical directions in the study of professional development. The principal ideas, inherent in those theories, compare to the modern approach to the professional development of the staff of organization in Russian sociology. The conclusions of the work clearly indicate the need for priority focus on the identity of the employee and his social characteristics in the process of organizing professional development of the staff of the organization.